THE EFFECTIVENESS OF USING MIND MAPPING STRATEGY TOWARD WRITING ABILITY FOR THE TENTH-GRADE STUDENTS AT SMA NEGERI 3 MOJOKERTO - Fahrur Rijal Ardiyanto (Pimpinan Cabang Muhammadiyah Kramat Jati, 2021)
Especially for students, writing become more important to be mastered in delivering their ideas during writing activity. To developing their ideas, students need strategy. It must be given high attention by teachers during teaching. One of the strategies to develop the ideas in writing is Mind Mapping strategy. Mind mapping have important role for students in writing recount text. Students will be easier to connect one event to other events. Same as the other strategy in learning process, mind mapping have some steps to do that. In this research, the researcher wants to measure The Effectiveness of Using Mind Mapping Strategy toward Writing Ability for The Tenth-Grade Students at SMA Negeri 3 Mojokerto in academic year 2016/2017. The result of t-test was 7,153. After got the t- test score, the reseracher compared it with t-table (df = n1 + n2 – 2 = 72; significance 5% = 0.05). The value of t-table was 1.666. It means that too is highest than table (7.153 > 1.666).